Production scheduling in a semiconductor wafer fabrication facility producing multiple product types with distinct due dates. - Yeong-Dae Kim (IEEE Transactions on robotics and automation)
Focuses on production scheduling in a semiconductor wafer fab producing multiple product types that have different due dates and different process flows. In the wafer fab, wafer lots are processed on serial and batch processing workstations, each of which consists of parallel identical machines. Machines in serial processing workstations process wafer lots one by one, while those in batch processing workstations process several wafer lots of the same recipe at the same time. What needs to be done for production scheduling are lot release control, lot scheduling, and batch scheduling. For these three decision problems, we develop several rules which use information such as order sizes (numbers of lots in orders) and processing status of the wafer lots. To evaluate these new rules, we use a simulation model in which the three decision problems are considered simultaneously. Simulation results show that the new rules work better than existing rules in terms of total tardiness of the orders